Predictive role of serum pepsinogen level as a serological marker of gastritis - Khan, Mansura; Bhuiyan, Tareq Mahmud; Rahman, Zeenat Farzana; Sarker, Abdullah Al Mamun; Nur, Jasmin; Siddiquee, Nadia; Akter, Mhabuba; Moniruzzaman, Mohammad (BIRDEM Medical Journal, 2026)
Background: Gastritis is a prevalent and insidious disorder that usually causes an inflammation of the gastric mucosa, which may be related to dietary habits, socioeconomic status and Helicobacter pylori infections. Serum pepsinogen I and II have been proposed as non-invasive biomarkers for gastric mucosal changes, including gastritis, particularly in association with H. pylori infection. This study aimed to evaluate the predictive role of serum pepsinogen levels as serological markers for gastritis. Methods: This cross-sectional study was performed in the Department of Gastrointestinal Hepatobiliary & Pancreatic Disorders (GHPD) and test performed in the Immunology Department of BIRDEM General Hospital, Dhaka from January to December of 2023. A total of 65 patients were selected by a random sampling technique and sent for endoscopy. Serum samples were collected to measure pepsinogen in those patients by using a Chemiluminescence Immunoassay (CLIA) and anti-H. pylori IgG by using Enzyme-Linked Immunosorbent Assay (ELISA). Results: Among 65 patients, 45 were diagnosed as gastritis and 20 were as non-gastritis following endoscopy. Thirty nine (39/65, 70.9%) were H. pylori IgG positive in the gastritis group and in the non-gastritis group 16 (29.1%) were H. pylori IgG positive. Both serum pepsinogen levels I (279.65±159.82) μg/L and pepsinogen II (22.61 ± 17.64) μg/L were significantly higher in the gastritis group than the non-gastritis group (p<0.05). The present study did not demonstrate a statistically significant association between H. pylori IgG seropositivity and serum pepsinogen I (p=0.269) and II (p=0.958) levels. Conclusion: Serum pepsinogens were increased among the gastritis group than the non-gastritis group though most of the patients were found positive of anti-H.pylori IgG. Therefore, compared to the H. pylori antibody test, serum pepsinogen is recommended as a superior non-invasive marker. BIRDEM Med J 2026; 16(1): 19-24